Fetal origins, childhood development, and famine: A bibliography and literature review - Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2011)
The human costs of famines outlast the famines themselves. An increasing body of research points to their adverse long-run consequences for those born or in utero during them. This paper offers an introduction to the burgeoning literature on fetal origins and famine through a review of research on one well-known case study and a bibliography of published work in the field generally.
Keywords: O1; I1; N3; 330